The development of the European Toolkit for the self-assessment of quality of life across the cancer care continuum (EUonQoL-Kit). - Nicklin, Emma; Bedding, Christopher; Alfieri, Sara; Apolone, Giovanni; Arndt, Volker; Bos, Nanne; Bredart, Anne; Brunelli, Cinzia; Caselli, Luana; Ciliberto, Gennaro; Rojas-Concha, Leslye; Couespel, Norbert; et al. (European Journal of Cancer, 2026)
The European Oncology Quality of Life (EUonQoL) project aims to develop a questionnaire toolkit (EUonQoL-Kit) to assess the quality of life (QoL) of cancer patients and survivors across Europe. The EUonQoL-Kit development used mixed-methods and a co-design approach. Data was collected in six countries (Denmark, France, Germany, Italy, Netherlands and UK). The target populations were patients in active treatment (A), survivors (B) and patients requiring palliative care (C). A review of existing QoL theoretical models produced an initial EUonQoL conceptual framework. Semi-structured interviews and a Delphi survey evaluated/modified the framework. Existing validated items were used to construct the toolkit, including Computer Adaptive Testing (CAT), where available. A usability study evaluated EUonQoL-Kit.v1. Data triangulation and consensus methodology guided EUonQoL-Kit.v2. The initial conceptual framework covered four multi-dimensional domains: physical, social and overall health, and psychological wellbeing. The interviews and Delphi survey included 75 and 155 participants, respectively. The domain 'healthcare experience' was identified and included in the framework. EUonQoL-Kit.v1 resulted in three static questionnaires, one for each target population (n items- A=75; B=67; C=79). Following usability testing with 53 participants, EUonQoL-Kit.v2 was produced via a multi-stakeholder consensus development panel, creating a shortened version (n items- A=50; B=50; C=44). Dynamic versions of these questionnaires were developed using the EORTC CAT Core system. EUonQoL-Kit is a novel toolkit developed to assess QoL across the cancer continuum and inform health policy within Europe. Its psychometric properties are currently being evaluated using data collected on more than 4200 patients across 32 countries. • The EUonQoL-Kit is a novel way to assess QoL and inform future EU cancer policies. • Over 277 patients, survivors and HCPs, from 6 countries developed the EUonQoL-Kit. • The EUonQoL-Kit was developed for static and dynamic assessment using CAT. • EUonQoL-Kit.v2 is being evaluated in 4200 + patients/survivors across 32 countries.